Memoria social de las lavanderías populares casos :“Chiriyacu”, “De los milagros” y “La Ermita” - Cajiao Oviedo, David Alejandro (2015)
The current document presents in detail the studies and the field investigation made with the main objective of revalue the public laundries. The results will be embodied in a magazine which is to be elaborated with its basis on the collected information. The presentation and revaluation of the public laundries in the city of Quito, M. D., is proposed based on several concepts and categories of communication, such as: popular and meeting spaces; social and individual memory; everyday life within social experiences; the traditions; the popular; the places and no-places; popular and everyday communication. Three specific cases are studied: La Ermita, located in San Roque neighbourhood; De Los Milagros, situated in La Loma Neighbourhood; and, Chiriyucu, sited in Chimbacalle neighbourhood. With the start point, and focus, in the neighbourhood where this spaces are located, a general overview of the environment in which the laundries, and the people, develop is presented. This document details specific aspects including not only the principal façade of the public laundries, but also the everyday life experienced nowadays and the description of what it was like in past years, furthermore, the accelerated chance that have been generated because of the globalization process inside this social space.